2023
DOI: 10.3390/cryst13050806
|View full text |Cite
|
Sign up to set email alerts
|

Schiff-Based Modified Bentonite Clay Composites for Wastewater Treatment: Experimental and DFT-Based Analysis

Sadaf Mutahir,
Fakhira Yaqoob,
Muhammad Asim Khan
et al.

Abstract: A new bentonite clay composite was synthesized by modifying bentonite clay and Schiff base (SB). The purpose of the composite was to eliminate methylene blue (MB) from wastewater. To characterize its efficacy, several spectroscopic techniques (UV-Visible spectroscopy, FTIR, SEM, and XRD) were used. The interactions between the adsorbent dose, pH, initial dye concentration, and contact duration were also tested to evaluate the adsorption capacity of the adsorbent. The results demonstrated that changes in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The pseudo-second-order kinetic models' t/q t with t exhibited a good linear relationship, as shown in Figures 11b and S1d. By calculating the fitting results, the parameters of the quasi-first-and second-order kinetic models were obtained [57], as presented in Table 3. The fitting results showed that the correlation coefficients R 2 of the quasi-second-order kinetic model for the molecular adsorption of CR by the ZC3 nanoparticles were 0.9932, 0.9966, 0.9967, and 0.9845.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…The pseudo-second-order kinetic models' t/q t with t exhibited a good linear relationship, as shown in Figures 11b and S1d. By calculating the fitting results, the parameters of the quasi-first-and second-order kinetic models were obtained [57], as presented in Table 3. The fitting results showed that the correlation coefficients R 2 of the quasi-second-order kinetic model for the molecular adsorption of CR by the ZC3 nanoparticles were 0.9932, 0.9966, 0.9967, and 0.9845.…”
Section: Adsorption Kineticsmentioning
confidence: 99%